Menyongsong Era Society 5.0: Strategi Manajemen Pendidik di SMK Pusat Keunggulan untuk Menciptakan Lulusan Siap Kerja - Fadia Puja Ainun; Heni Setya Mawarni; Hesti Puspita Sari; Nida Nimatul Fauzah (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze the management of educators in schools of excellence through the use of interview techniques. Where schools of excellence center have a vital role in providing high quality education and become models for other schools. Therefore, this study aims to gain an in-depth understanding of various aspects of educator management that play a role in improving the quality of education in these schools. The interview session was carried out by contacting the selected respondents, then asking several questions contained in the interview instrument. During the interview, respondents responses and views were recorded with their consent to ensure the integrity of the data obtained. The data obtained through interviews will be analyzed qualitatively to identify challenges, best practices, and opportunities for improvement in teacher management in these schools. The results of this study are expected to provide an in-depth understanding of educator management in schools with centers of excellence. The findings in this study will provide valuable insights for decision making and strategy development in an effort to improve effective educator management in schools of centers of excellence as well as improve the overall quality of education.